Topiramate improves neurovascular function, epidermal nerve fiber morphology, and metabolism in patients with type 2 diabetes mellitus - Boyd A (Diabetes, Metabolic Syndrome and Obesity, 2010)
Amanda L Boyd, Patricia M Barlow, Gary L Pittenger, Kathryn F Simmons, Aaron I VinikDepartment of Internal Medicine, Eastern Virginia Medical School, Norfolk, VA, USAPurpose: To assess the effects of topiramate on C-fiber function, nerve fiber morphology, and metabolism (including insulin sensitivity, obesity, and dyslipidemia) in type 2 diabetes.Patients and methods: We conducted an 18-week, open-label trial treating patients with topiramate. Twenty subjects with type 2 diabetes and neuropathy (61.5 ± 1.29 years; 15 male, 5 female) were enrolled and completed the trial. Neuropathy was evaluated by total neuropathy scores, nerve conduction studies, quantitative sensory tests, laser Doppler skin blood flow, and intraepidermal nerve fibers in skin biopsies.Results: Topiramate treatment improved symptoms compatible with C-fiber dysfunction. Weight, blood pressure, and hemoglobin A1c also improved. Laser Doppler skin blood flow improved significantly after 12 weeks of treatment, but returned to baseline at 18 weeks. After 18 weeks of treatment there was a significant increase in intraepidermal nerve fiber length at the forearm, thigh, and proximal leg. Intraepidermal nerve fiber density was significantly increased by topiramate in the proximal leg.Conclusion: This study is the first to demonstrate that it is possible to induce skin intraepidermal nerve fiber regeneration accompanied by enhancement of neurovascular function, translating into improved symptoms as well as sensory nerve function. The simultaneous improvement of selective metabolic indices may play a role in this effect, but this remains to be determined.Keywords: diabetic neuropathy, skin blood flow, skin biopsy, diabetes